DEVELOPMENT OF AUGMENTED REALITY (AR) BASED APPLICATION FOR INTRODUCTION TO BIOMOLECULES IN UNDERSTANDING THE DRUG DISCOVERY OF SARS-COV-2 ANTIVIRUS - Wiguna Kusuma Paksi, Pinantun
Visualizing biomolecules and compound structures in three dimensions (3D) is challenging for students. Virtual Reality (VR) is a promising technology in the revolution of STEM (Science, Technology, Engineering, and Mathematics) education. However, most VR tools require expensive hardware, posing a cost barrier for large-scale usage. Therefore, it is necessary to develop an augmented reality (AR) model as an alternative learning medium for students. AR is chosen because smartphones have become a primary necessity everywhere, eliminating the need for costly VR hardware. AR has been extensively used in various cases involving compound and molecular structures, but these applications are typically standalone, requiring users to download and install them, which can be impractical. Hence, the development of a web-based AR learning medium, where users only need to access a website without downloading or installing an application, provides a more convenient solution. The developed web-based AR model was tested in a classroom setting. Surveys from students and the general public were used to assess the effectiveness of this AR web learning model. The results from respondents showed satisfaction levels of 78.40 and 77.60 in terms of material delivery and presentation, indicating a good reception. Additionally, the average user comprehension score was 61.18, which can be categorized as an understanding of the material. Thus, it can be concluded that the teaching method using this web-based AR model has met the functional requirements effectively.